Releasing trapped excitons in 2D perovskites via pressure annealing: a cooperative interplay between lattice strain and the electronic structure - Freitas, Andre L.M.; Caturello, Naidel A.M.S.; Tofanello, Aryane; Kaneko, Ulisses F. [UNESP]; Correa, Lucas E.; dos Reis, Ricardo D.; Ferreira, Fabio F.; Dalpian, Gustavo M.; Souza, Jose A. (Royal Society of Chemistry (RSC), 2024)
Characteristic photon emissions in low-dimensional hybrid perovskites are strongly related to inherent distortions in the crystal lattice. These cooperative distortions, influenced by organic spacers and the confined BX6 octahedral arrangement, allow for the manipulation and control of the emitted photon energy and its nature. Herein, we observed a complex dynamic where photon emissions at both low and high energies emerge, depending on octahedral distortion and the application of hydrostatic pressure. Our results demonstrated that samples featuring different octahedral sizes and distortions but having a common organic spacer (BA2MAPb2Br7 and BA2MAPb2I7) showed low-energy photon emission attributed to self-trapped excitons (STEs), which can be tuned towards free exciton (FE) states through pressure annealing. Experimental and theoretical results revealed that octahedral distortions in 2D perovskites played a crucial role in controlling emission, disclosing their complex structure and electronic relationship.